Metaphor and Lexical Semantics - Michael Glanzberg (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
ABSTRACT: This paper shows that several sorts of expressions cannot be interpreted metaphorically, including determiners, tenses, etc. Generally, functional categories cannot be interpreted metaphorically, while lexical categories can. This reveals a semantic property of functional categories, and it shows that metaphor can be used as a probe for investigating them. It also reveals an important linguistic constraint on metaphor. The paper argues this constraint applies to the interface between the cognitive systems for language and metaphor. However, the constraint does not completely prevent structural elements of language from being available to the metaphor system. The paper shows that linguistic structure within the lexicon, specifically, aspectual structure, is available to the metaphor system.
Keywords: philosophy; linguistics